THE CONSUMER DECISION OF CHANGES PURCHASING GLASSES IN OPTICAL NAOMY YEAR 2019 - Wahjoe Handini Dina; Ita Puji Lestari (Universitas Ngudi Waluyo, 2020)
The purchase decision process is the process through which consumers when buying a product. It can be seen as a special form of cost-benefit analysis. This study is about knowing the decision of consumers in the purchase of glasses in the form of design, price, services, promotions and materials. The type of research is descriptive research conducted with the main objective to create a picture or a description of a situation objectively with the approach used in the study is Cross-sectional namely researchers put through observation or measurement variables at one time. Research in Optics Naomy shows that in the period July - September 2019 there were 32 respondents consisting of 19 (59.4%) of female respondents and 13 (40.6%) male respondents - men. Most aged 15-25 years as many as 26 people (81.3%), not married as many as 26 people (81.3%), student / student as many as 23 people (71.9%) and earn less than Rp 1 million, 00 as many as 26 people (81.3%). The majority of respondents in the optical Naomy declare eyeweare design is Good (62,5%), the price of the glasses in the optical Naomy is Less Suitable (65,6%), services in the optical Naomy is Good (65,6%), promotion in the optical Naomy is Good (62,5%), materials in optical glasses Naomy Good (56,2%). The decision making process of consumers in the purchase of glasses in the optical Weleri in this study prefer the design (22%) and services (21.8%), materials (21.2%), price (19.8%) and promotions (15.2 %).Â